Heart University: a new online educational forum in paediatric and adult congenital cardiac care. The future of virtual learning in a post-pandemic world?. (13th April 2020) - Tretter, Justin T; Windram, Jonathan; Faulkner, Theresa; Hudgens, Michelle; Sendzikaite, Skaiste; Blom, Nico A; Hanseus, Katarina; Loomba, Rohit S; McMahon, Colin J; Zheleva, Bistra; Kumar, Raman Krishna; Jacobs, Jeffrey P; et al.
Abstract: Online learning has become an increasingly expected and popular component for education of the modern-day adult learner, including the medical provider. In light of the recent coronavirus pandemic, there has never been more urgency to establish opportunities for supplemental online learning. Heart University aims to be "the go-to online resource" for e-learning in CHD and paediatric-acquired heart disease. It is a carefully curated open access library of paedagogical material for all providers of care to children and adults with CHD or children with acquired heart disease, whether a trainee or a practising provider. In this manuscript, we review the aims, development, current offerings and standing, and future goals of Heart University.